Performance of Public Information in Improving Employee Performance at the One Stop Service Office in Palangka Raya City - Djungan, Timothy Dehen L. (Indonesian Journal of Economic & Management Sciences, 2024)
This study explores the impact of organizational culture, HR strategy, and employee performance at the Kantor Pelayanan Satu Pintu in Palangka Raya. HR innovation arises from a creative learning process, supported by empathetic leadership and a strong organizational culture. A strategic HRM approach fostering a culture of achievement is essential for enhancing employee performance. Using a quantitative approach with the SEM-PLS method and 100 respondents, the results show that organizational culture significantly affects information quality and employee performance. Performance and information quality also have a partial yet significant impact on employee performance. Aligning information quality with organizational strategy further strengthens performance outcomes. The findings emphasize the interconnection of organizational culture as the foundation, performance quality for execution, and information quality for decision-making. These factors collectively improve organizational effectiveness. Future research should consider internal dynamics, including motivation shifts and innovative performance, to deepen the understanding of organizational development.